Alkylation Reactions with Alkylsulfonium Salts - Tian, Ze-Yu; Ma, Yu; Zhang, Cheng-Pan (Synthesis, 2022)
The application of alkylsulfonium salts as alkyl-transfer reagents in organic synthesis has reemerged over the past few years. Numerous heteroatom- and carbon-centered nucleophiles, alkenes, arenes, alkynes, organometallic reagents, and others are readily alkylated by alkylsulfonium salts under mild conditions. The reactions feature convenience, high efficiency, readily accessible and structurally diversified alkylation reagents, good functional group tolerance, and a wide range of substrate types, allowing the facile synthesis of various useful organic molecules from commercially available building blocks. This review summarizes alkylation reactions using either isolated or in situ formed alkylsulfonium salts via nucleophilic substitution, transition-metal-catalyzed reactions, and photoredox processes.1 Introduction2 General Methods for the Synthesis of Alkylsulfonium Salts3 Electrophilic Alkylation Using Alkylsulfonium Salts4 Transition-Metal-Catalyzed Alkylation Using Alkylsulfonium Salts5 Photoredox-Catalyzed Alkylation Using Alkylsulfonium Salts6 Conclusion
Keywords: alkylsulfonium; alkylation; nucleophiles; metal-catalyzed; photoredox